South Asia Economic Focus, Spring 2016 : Fading Tailwinds - World Bank (2016)
South Asia by now has consolidated its position as fastest growing developing region in the world. Against the backdrop of relative external stability and some monetary policy space, growth is expected to continue a gradual acceleration on the back of strong investment performance and a return to solid contributions from export growth. India remains the motor of the region and on its way closer to 8 percent real GDP growth, though on a relatively more gradual path than previously anticipated. At the same time, economies across the region will have to tackle fading tailwinds and face ever more binding domestic constraints in the form of persistently high fiscal deficits together with high debt levels as well as some vulnerabilities in the financial sector. The focus section of this report will delve deeper into evaluating the quality of fiscal consolidation and policy, trying to assess short and longer term impact across major South Asian economies.